A Study on the Importance of Learner Ideal Self to the Success in Learning English of the Learners at the Border Guard Academy = Một nghiên cứu về tầm quan trọng của lý tưởng người học đối với sự thành công trong việc học tiếng Anh tại Học viện Biên Phòng - Phùng, Thị Phương Lan (University of Languages and International Studies, 2017)
Drawing on the model L2 Motivational Self SystembyDörnyei(2005), thisstudy explores the importance of the learner ideal selfto the success in studying English of the learners at the Border Guard Academy using survey research methodology. The participants are 100 freshmen in the Border Guard Academy, Sontay, Hanoi, where I am working. Two data collection instruments are employed: questionnaires and individual open-ended interviews. The findings show that the learner ideal selfis the key to success in English studying of the learners at the Border Guard Academy. Despite the existence of ideal selfin the students’ mind, the number of students with ideal selfis still humble, which accounts for the border officers’ inefficiency in solving English using cases. The study puts forward practical suggestions to all the academy, the teachers of English and the students with a view to improving English teaching and learning at the academy. The most important proposal is disseminating the role of the learner ideal selfto their own success in English studying and the demand for buiding up, maintaining and motivating the ideal selffor the learners at the Border Guard Academy.